Near-infrared spectral variation in Ryugu particles and implication for rapid space weathering by solar UV radiation - S. Furukawa; T. Okada; K. Hatakeda; R. Kanemaru; K. Yogata; T. Yada; M. Abe; T. Usui; C. Pilorget; V. Hamm; R. Brunetto; D. Loizeau; et al. (Scientific Reports)
Abstract The 2.7 µm absorption band, represented by OH groups, in the near-infrared reflectance spectra of primitive Solar System bodies could be an indicator of the cause and degree of space weathering. We compared the absorption bands of particles sampled from the surface (chamber A) and the excavated subsurface (chamber C) on the C-type asteroid Ryugu by the JAXA Hayabusa2 mission. We developed a fitting method using multiple Gaussians to precisely calculate the band’s peak position and depth, providing more reliable information on space weathering effects. We found that the chamber A particles were divided into groups Aα with shorter peak position and deeper band depth (non or poorly space weathered) and Aβ with longer peak position and shallower band depth (rich in space weathering). Chamber C particles are partly show intermediate characteristics between Aα and Aβ, which might imply weak space weathering by solar UV radiation during three months between the excavation by impact experiment and sampling by Hayabusa2. Supplementally, our preliminary experiment of UV irradiation to Ivuna meteorite showed decrease of 2.7 µm band depth and longward shift of the peak position, and further study is needed to investigate the effect of short-term UV space weathering on carbonaceous asteroids.